Actions for Professional Development to Enhance Competence in Communicating Scientific Results - Alexeis Ruíz-Díaz; Yamila Roque-Doval; Mayra Rodríguez-Ruíz (Universidad Nacional, Costa Rica, 2017)
The main goal of this research is to propose an action plan for professional development to enhance competence in communicating scientific results in teachers of municipal secondary schools. The research is part of a complementary methodological approach that combines different quantitative and qualitative methods based on specific objectives. The diagnosis was made at the Municipal University Center of Sagua La Grande, with a sample of 25 teachers who are members of the Industrial Engineering career staff at the institution, attached to the Central University "Marta Abreu" of Las Villas, Cuba. Regularities were found from the stage of the initial diagnosis of professional development needs and the level in which the "competence in communicating scientific results" variable was. With this information justifying the purposes of this research, a process was designed following a systemic approach, and the practical result was the proposal of the organization and design of an action plan for development through postgraduate education forms during the implementation phase.